Effect of NaNO2 and C6H15NO3 Synergistic Admixtures on Steel-Rebar Corrosion in Concrete Immersed in Aggressive Environments - Joshua Olusegun Okeniyi; Abimbola Patricia Idowu Popoola; Cleophas Akintoye Loto; Olugbenga Adeshola Omotosho; Stanley Okechukwu Okpala; Idemudia Joshua Ambrose (Advances in Materials Science and Engineering)
This paper studies effect of different combinations of NaNO2 (sodium nitrite) and C6H15NO3 (triethanolamine (TEA)), as synergistic admixtures in concrete immersed in NaCl and in H2SO4 test environments, on the corrosion of the concrete reinforcing steel (rebar). Although statistically analysed electrochemical test results confirmed NaNO2 effectiveness, synergistic combinations of 4 g NaNO2 + 4 g C6H15NO3 in NaCl medium and of 2 g NaNO2 + 6 g C6H15NO3 in H2SO4 medium were also highly effective at inhibiting rebar corrosion. Synergistic parameter analyses showed that the effective synergistic admixtures that inhibited concrete steel-rebar corrosion in their respective medium were the NaNO2 and C6H15NO3 combinations that exhibited synergistic interactions of cooperative adsorption on steel-rebar. These support the suitability of requisite concentration of triethanolamine as additive admixture with sodium nitrite for steel-rebar corrosion mitigation, which is potent with reduced environmental effects, in concrete immersed in NaCl and in H2SO4 corrosive media.